Ab initio molecular dynamics of hydrogen on tungsten surfaces. Issue 13 (21st December 2020) - Rodríguez-Fernández, Alberto; Bonnet, Laurent; Larrégaray, Pascal; Muiño, Ricardo Díez
Abstract : The dissociation process of hydrogen molecules on W (110) was studied using density functional theory and classical molecular dynamics. Abstract : The dissociation process of hydrogen molecules on W(110) was studied using density functional theory and classical molecular dynamics. We have calculated the dissociation probability for molecules with energies below 300 meV and analyzed the dynamics of the adsorption process. Our results show that the fate of each trajectory is determined at distances relatively far from the surface, at roughly 2–2.5 Å. This distance varies slightly with the initial kinetic energy of the molecule. Part of our simulations include van der Waals dispersion effects in the interaction between molecule and surface. We present a comparison between these results and other theoretical and experimental results previously published. The inclusion of the van der Waals term provokes an increase in the far-distance attraction that is compensated by a stronger repulsion at short distances. The combination of both effects appreciably decreases the value of the dissociation probability. The successful comparison of our results with experimental information confirms that the methodology employed can be considered as a rich and accurate instrument to study the dissociation of hydrogen on surfaces.